PENGARUH KUALITAS LAYANAN, KESADARAN PAJAK, PEMERIKSAAN PAJAK, PENGETAHUAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KECAMATAN DELANGGU - Purnama Siddi; Adi Hartopo; Endang Masitoh (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2020)
This study aims to determine the effect of service quality, tax awareness, tax audits, tax knowledge, and tax sanctions on tax payer compliance. The population in this study are private motor vehicle taxpayers registered in SAMSAT in Delanggu sub-district. The sample in this study is the motor vehicle taxpayer who is domiciled in the Delanggu sub-district. The sampling technique in the study is the accidental sampling method, which is a method based on coincidence that anyone who is subject to PKB accidentally encountered by the researcher can be sampled if the PKB mandatory that happens to be encountered is assessed right as a data source. Data analysis techniques in this study used multiple linear regression. This study found that the compliance of individual taxpayers was influenced by tax awareness, tax audits, tax knowledge. Meanwhile, service quality and tax sanctions do not affect the compliance of motor vehicle taxpayers in Delanggu sub-district.